Design, synthesis, and evaluation of chiral thiophosphorus acids as organocatalysts - Winters, Karen R.; Montchamp, Jean-Luc (Beilstein Journal of Organic Chemistry, 2022)
A series of P-stereogenic chiral phosphorus acids (CPAs) were synthesized to determine the requirements for efficient asymmetric organocatalysis. In order to eliminate the need for C2-symmetry in common CPAs, various scaffolds containing C1-symmetrical thiophosphorus acids were chosen. These new compounds were synthesized and evaluated in the asymmetric transfer hydrogenation of 2-phenylquinoline. Although the efficacy of the thiophosphorus acids was disappointing for this reaction, the work should be useful for developing structural design elements.
Keywords: asymmetric; heterocycles; organocatalysis; phosphorus; synthesis